Method for recycling iron and manganese and preparing cementing material by synergistically utilizing electrolytic manganese residues and waste incineration fly ash and product thereof

By calcining phosphogypsum with electrolytic manganese slag and mixing it with municipal sludge and waste incineration fly ash for pyrolytic carbonization, the resource utilization problem of electrolytic manganese slag and waste incineration fly ash is solved, and efficient recycling of iron and manganese resources is achieved and Preparation of high-performance gelling materials improves resource utilization and environmental protection.

CN119219068APending Publication Date: 2024-12-31CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411323010.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

There are technical challenges in the treatment and resource utilization of electrolytic manganese slag and waste incineration fly ash, which leads to environmental pollution and waste of resources, and the existing technology is insufficient in efficiency and environmental protection.

Method used

By mixing phosphogypsum with electrolytic manganese slag, activated slag material is formed, and then mixed with municipal sludge and waste incineration fly ash for pyrolytic carbonization, iron and manganese resources are recovered, and highly active gelled materials are prepared.

Benefits of technology

It has achieved efficient recycling of iron and manganese resources, and prepared gelled materials with a single-axis compressive strength of up to 35MPa. The process is simple and the raw materials are limited, which reduces the processing cost and improves resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219068A_ABST
    Figure CN119219068A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling iron and manganese and preparing a cementing material by synergistically utilizing electrolytic manganese residues and waste incineration fly ash and a product thereof, the method comprises the following steps: mixing ardealite and electrolytic manganese residues, and uniformly stirring to obtain gypsum manganese residues; calcining the gypsum manganese slag to obtain activated slag; mixing the activated slag material, municipal sludge and waste incineration fly ash, and uniformly stirring to obtain an initial roasting material; the initial roasting material is subjected to continuous pyrolysis carbonization, pyrolysis flue gas dust recycled in the first pyrolysis process is coarse iron powder, pyrolysis flue gas dust recycled in the second pyrolysis process is coarse manganese powder, solid residues obtained in the second pyrolysis process are gelatinized activated residues, the gelatinized activated residues are ground into powder, and the cementing material is obtained. The preparation process is simple, and the required raw materials are only electrolytic manganese residues, waste incineration fly ash and common industrial solid wastes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid waste resource utilization, and in particular to a method for recovering iron and manganese and preparing a cementitious material by synergistically utilizing electrolytic manganese slag and garbage incineration fly ash, and a product thereof. Background Art

[0002] Electrolytic manganese slag is a solid waste generated during the production of electrolytic manganese. Manganese ore powder is leached with sulfuric acid and neutralized with ammonia to prepare manganese sulfate solution. After filtration, the industrial waste slag containing water-soluble salts such as sulfate and ammonium salt is electrolytic manganese slag. The average grade of manganese ore in my country is only about 12%, so when producing 1 ton of metallic manganese, 8 to 10 tons of manganese slag will be produced. At present, the amount of electrolytic manganese slag stockpiled in my country has exceeded 100 million tons, and more than 10 million tons are added each year. The content of heavy metals and soluble salt compounds in manganese slag is high. If not handled properly, it will cause serious pollution to the environment. Electrolytic manganese slag contains high concentrations of heavy metals such as manganese, chromium, and nickel. These heavy metals are not easily degraded in the environment and can accumulate through the food chain, causing long-term effects on human health and ecosystems. Heavy metals in manganese slag can enter the soil through surface runoff or infiltration, affecting soil fertility, causing plant growth stagnation, or even death. In an environment that has been polluted by manganese slag for a long time, biodiversity will be significantly reduced, and the stability and self-repair ability of the ecosystem will be weakened.

[0003] The environmental hazards of electrolytic manganese slag cannot be ignored. Through resource utilization, it can not only reduce environmental pollution, but also realize the recycling of resources and promote sustainable development. The heavy metal recovery technology in electrolytic manganese slag currently mainly includes chemical harmless technology, pyrolysis technology, wet harmless and resource treatment technology, biological harmless technology, external electric field harmless technology, preparation of adsorption material technology, etc. The effects of these technologies have their own characteristics. The selection of appropriate technology needs to consider the specific composition, treatment cost, environmental impact and feasibility of resource recovery of electrolytic manganese slag. In general, the treatment and resource utilization of electrolytic manganese slag still face technical challenges, and further research and development are needed to achieve more efficient and environmentally friendly treatment methods.

[0004] Waste incineration fly ash is a hazardous waste generated during the incineration of domestic waste. With the rapid increase in the amount of urban domestic waste, the amount of fly ash produced is also increasing. Fly ash contains high concentrations of toxic and harmful substances such as heavy metals and dioxins. If not properly handled, it will pose a serious threat to the environment and human health. Research on the synergistic utilization of electrolytic manganese slag and waste incineration fly ash can promote the development of solid waste treatment technology and promote the construction of a circular economy, which is in line with the current strategic requirements of sustainable development and green development. By in-depth research on the resource utilization of these two wastes, it can provide reference and reference for solving similar environmental and resource problems of industrial solid waste. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a method and product for synergistically utilizing electrolytic manganese slag and waste incineration fly ash to recover iron and manganese and prepare cementitious materials.

[0006] Technical solution: The present invention provides a method for recovering iron and manganese and preparing a cementitious material by synergistically utilizing electrolytic manganese slag and waste incineration fly ash, comprising the following steps:

[0007] (1) mixing phosphogypsum and electrolytic manganese slag, and stirring evenly to obtain gypsum manganese slag;

[0008] (2) calcining the gypsum manganese slag to obtain an activated slag material;

[0009] (3) Mixing the activated slag, municipal sludge, and waste incineration fly ash, stirring evenly, to obtain an initial roasting material;

[0010] (4) The initial roasted material is continuously pyrolyzed and carbonized. The pyrolysis flue gas dust recovered in the first pyrolysis process is coarse iron powder, and the pyrolysis flue gas dust recovered in the second pyrolysis process is coarse manganese powder. The solid slag obtained in the second pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelled material.

[0011] Furthermore, in step (1), the mass ratio of phosphogypsum to electrolytic manganese slag is 20 to 60:100.

[0012] Furthermore, the calcination time in step (2) is 0.5 to 1.5 hours, and the calcination temperature is 450 to 850°C.

[0013] Furthermore, in step (3), the mass ratio of the activated slag, municipal sludge and waste incineration fly ash is 20-50:30-60:100.

[0014] Furthermore, the temperature of the first pyrolysis in step (4) is 350-550° C., and the time is 0.25-1.25 hours.

[0015] Furthermore, the temperature of the second pyrolysis in step (4) is 1150-1250° C., and the time is 0.25-1.25 hours.

[0016] The present invention also provides coarse iron powder prepared according to the method.

[0017] The present invention also provides coarse manganese powder prepared according to the method.

[0018] The invention also provides a gel material prepared according to the method.

[0019] Furthermore, the uniaxial compressive strength of the gel material is 26-35 MPa.

[0020] Reaction mechanism: Phosphogypsum and electrolytic manganese slag are mixed. During the stirring process, the soluble fluorine, phosphorus and sulfate substances in the phosphogypsum are adsorbed in the electrolytic manganese slag particle minerals and undergo a stabilization transformation to form stable fluoride, phosphate and sulfate minerals. During the calcination process, the calcium sulfate dihydrate in the phosphogypsum decomposes, releases water vapor and forms anhydrous calcium sulfate. The released water vapor can not only promote the reaction of anhydrous calcium sulfate with aluminosilicate minerals and other inorganic salts in the electrolytic manganese slag particles to form a stable intermixed mixture of calcium aluminosilicate salt minerals and phosphate minerals through thermal excitation, but also promote the thermal decomposition of calcium sulfate to release acidic gas, thereby further accelerating the release of iron and manganese substances in the electrolytic manganese slag. Activated slag, municipal sludge and waste incineration fly ash are mixed. During the stirring process, the organic matter and other inorganic salt substances in the municipal sludge and the inorganic chloride and hydroxide in the waste incineration fly ash diffuse into the activated slag, combine with the released iron and manganese substances and react with the silicon-aluminum-calcium-based minerals in the activated slag. The initial roasting material is continuously pyrolyzed and carbonized. In the first pyrolysis process, the organic matter in the municipal sludge is pyrolyzed to form carbon-based materials and release active hydrocarbon gas. The active hydrocarbon gas can induce the chloride salt in the waste incineration fly ash to combine with the iron in the activated slag, and a carbon thermal chlorination reaction occurs, forming ferric chloride substances that volatilize into the flue gas, and are recovered through the flue gas to form coarse iron powder, while the phosphate and gypsum substances introduced into the municipal sludge by the phosphogypsum can inhibit the reaction and combination of aluminum and chlorine. In the secondary pyrolysis process, the manganese in the activated slag combines with the chloride salt and volatilizes on the carbon-based surface, and is recovered through the flue gas to form coarse manganese powder. In the thermal decomposition process of the slag after the secondary pyrolysis activation, the silicon-aluminum-calcium-based materials fully react with other inorganic salt minerals and activate each other complementary to form a highly active cementitious material.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the preparation process of the present invention is simple, and the raw materials required are only electrolytic manganese slag, waste incineration fly ash and general industrial solid waste. The iron and manganese resources are recovered from the electrolytic manganese slag through pre-batch, calcination activation, secondary batching and pyrolysis carbonization process, and a high-activity gelling material is prepared. The ferric chloride content of the prepared crude iron powder is up to 94% or more, the manganese chloride content of the prepared crude manganese powder is up to 85% or more, and the maximum uniaxial compressive strength of the prepared high-activity gelling material can reach 35MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure is a flow chart of the processing method of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0024] Phosphogypsum: Phosphogypsum is taken from Guizhou Xifeng Phosphate Fertilizer Plant. The phosphogypsum sample mainly contains 52.70% SO3, 37.01% CaO, 4.37% SiO2, 2.07% Al2O3, 1.63% P2O5 and other components (unavoidable impurities and loss on ignition).

[0025] Electrolytic manganese slag: The electrolytic manganese slag is taken from Guizhou Energy Mining Manganese Industry Group Co., Ltd., mainly including 23.52% SO3, 13.17% SiO2, 15.21% CaO, 13.09% Fe2O3, 6.82% Al2O3, 10.21% MnO, 2.96% K2O, 1.55% MgO, 0.86% TiO2 and other components (inevitable impurities and ignition loss).

[0026] Municipal sludge: Municipal sludge was taken from the sewage treatment plant in Changshu Southeast Economic Development Zone. The main chemical components include: 64.17% SiO2, 13.56% Al2O3, 4.86% Fe2O3, 3.75% P2O5, 2.34% CaO and other components (loss on ignition and other inevitable impurities).

[0027] Waste incineration fly ash: Waste incineration fly ash is provided by the Second Municipal Waste Incineration Power Plant in Changshu, Jiangsu Province, mainly including 38.14% CaO, 24.05% Cl, 10.21% SO3, 12.15% Na2O, 6.21% K2O, 3.17% SiO2, 1.41% Fe2O3, 1.19% Al2O3 and other components (loss on ignition and other inevitable impurities).

[0028] Example 1 Effect of the mass ratio of phosphogypsum and electrolytic manganese slag on the recovery of iron and manganese and the strength properties of the prepared cementitious material

[0029] The phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 5:100, 10:100, 15:100, 20:100, 40:100, 60:100, 65:100, 70:100, and 75:100, and stirred evenly to obtain gypsum manganese slag. The gypsum manganese slag is calcined to obtain an activated slag material, wherein the calcination time is 0.5 hours and the calcination temperature is 450° C. The activated slag material, municipal sludge, and waste incineration fly ash are mixed in a mass ratio of 20:30:100, and stirred evenly to obtain an initial roasting material. The initial roasting material is subjected to continuous pyrolysis and carbonization. The pyrolysis temperature is first increased to 350°C for a primary pyrolysis, and the primary pyrolysis time is 0.25 hours. The pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder. The pyrolysis temperature is then increased to 1150°C for a secondary pyrolysis, and the secondary pyrolysis time is 0.25 hours. The pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder. The solid slag obtained from the secondary pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelled material.

[0030] Strength performance test: The cementitious material of the present invention is made into the tested mortar, wherein the sand used is the ISO standard sand specified in the "Test Method for Strength of Cement Mortar (ISO Method)" GB / T 17671-1999, and tap water is used. The preparation of mortar, the preparation of test pieces, the curing of test pieces, and the measurement of the compressive strength of 28d test pieces are all carried out in accordance with the "Test Method for Strength of Cement Mortar (ISO Method)" GB / T 17671-1999 standard.

[0031] Iron content detection: According to "Ferric Chloride for Water Treatment Agents" (GB / T 4482-2018), the iron content in the crude iron powder was tested, and then multiplied by the coefficient 162.5 / 56 to determine the ferric chloride content in the crude iron powder.

[0032] Manganese content detection: According to the "Determination of manganese content in manganese ore by potentiometric titration and ammonium ferrous sulfate titration method" (GB / T1506-2016), the manganese content in the crude manganese powder is detected, and then multiplied by the coefficient 125.84 / 54.94 to determine the manganese chloride content in the crude manganese powder.

[0033] The test results of this embodiment are shown in Table 1.

[0034] Table 1 Effect of mass ratio of phosphogypsum and electrolytic manganese slag on iron and manganese recovery and strength properties of prepared cementitious materials

[0035]

[0036]

[0037] It can be seen from Table 1 that when the mass ratio of phosphogypsum to electrolytic manganese slag is less than 20:100 (such as in Table 1, the mass ratio of phosphogypsum to electrolytic manganese slag = 15:100, 10:100, 5:100 and lower ratios not listed in Table 1), less phosphogypsum is added, the reaction of phosphogypsum and electrolytic manganese slag is insufficient, and the release of iron and manganese substances in the electrolytic manganese slag is slowed down, which reduces the recovery efficiency of iron and manganese, resulting in the ferric chloride content in the crude iron powder, the manganese chloride content in the crude manganese powder, and the uniaxial compressive strength of the cementitious material all significantly decreasing with the decrease of the mass ratio of phosphogypsum to electrolytic manganese slag. When the mass ratio of phosphogypsum to electrolytic manganese slag is between 20 and 60:100 (as in Table 1, the mass ratio of phosphogypsum to electrolytic manganese slag = 20:100, 40:100, 60:100), phosphogypsum and electrolytic manganese slag are mixed, and the soluble fluorine, phosphorus and sulfate substances in the phosphogypsum are adsorbed in the electrolytic manganese slag particle minerals during the stirring process, and stabilized and transformed to form stable fluoride, phosphate and sulfate minerals. During the calcination process, the dihydrate calcium sulfate in the phosphogypsum decomposes, releases water vapor and forms anhydrous calcium sulfate. The released water vapor can not only promote the reaction of anhydrous calcium sulfate with aluminosilicate minerals and other inorganic salts in the manganese slag particles through thermal excitation to form a stable calcium aluminosilicate salt mineral and phosphate mineral intermixed mixture, but also promote the thermal decomposition of calcium sulfate to release acidic gas, thereby further accelerating the release of iron and manganese substances in the electrolytic manganese slag. Finally, the ferric chloride content in the crude iron powder is higher than 83%, the manganese chloride content in the crude manganese powder is higher than 75%, and the uniaxial compressive strength of the cementitious material is higher than 26MPa. When the mass ratio of phosphogypsum to electrolytic manganese slag is greater than 60:100 (as in Table 1, the mass ratio of phosphogypsum to electrolytic manganese slag = 65:100, 70:100, 75:100 and higher ratios not listed in Table 1), the phosphogypsum dosage is too much and the material matching is unbalanced, resulting in the ferric chloride content in the crude iron powder, the manganese chloride content in the crude manganese powder, and the uniaxial compressive strength of the cementitious material are significantly reduced as the mass ratio of phosphogypsum to electrolytic manganese slag further increases.

[0038] Therefore, in summary, considering efficiency and cost, when the mass ratio of phosphogypsum to electrolytic manganese slag is 20-60:100, it is most conducive to improving the performance of the prepared magnesium-based cementitious material and the recovery rate of iron and manganese.

[0039] Example 2 Effect of the mass ratio of activated slag, municipal sludge and waste incineration fly ash on the recovery of iron and manganese and the strength properties of the prepared cementitious material

[0040] The phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 60:100 and stirred evenly to obtain gypsum manganese slag. The gypsum manganese slag is calcined to obtain an activated slag material, wherein the calcination time is 1 hour and the calcination temperature is 650°C. The activated slag, municipal sludge and waste incineration fly ash are mixed in a mass ratio of 5:30:100, 10:30:100, 15:30:100, 20:15:100, 20:20:100, 20:25:100, 20:30:100, 35:30:100, 50:30:100, 20:45:100, 35:45:100, 50:45:100, 20:60:100, 35:60:100, 50:60:100, 50:65:100, 50:70:100, 50:75:100, 55:60:100, 60:60:100 and 65:60:100, and stirred evenly to obtain an initial roasting material. The initial roasting material is subjected to continuous pyrolysis and carbonization. The pyrolysis temperature is first increased to 450°C for a primary pyrolysis, and the primary pyrolysis time is 0.75 hours. The pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder. The pyrolysis temperature is then increased to 1200°C for a secondary pyrolysis, and the secondary pyrolysis time is 0.75 hours. The pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder. The solid slag obtained from the secondary pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelled material.

[0041] The strength performance test, iron content test, and manganese content test are the same as those in Example 1. The test results of this example are shown in Table 2. Table 2 Effect of the mass ratio of activated slag, municipal sludge, and garbage incineration fly ash on iron and manganese recovery and strength performance of the prepared cementitious material

[0042]

[0043]

[0044] It can be seen from Table 2 that when the mass ratio of activated slag, municipal sludge and waste incineration fly ash is less than 20:30:100 (as in Table 2, the mass ratio of activated slag, municipal sludge and waste incineration fly ash = 20:25:100, 20:20:100, 20:15:100, 15:30:100, 10:30:100, 5:30:100 and lower ratios not listed in Table 2), less activated slag and municipal sludge are added, and the reaction between activated slag, municipal sludge and waste incineration fly ash is insufficient, resulting in the ferric chloride content in the coarse iron powder, the manganese chloride content in the coarse manganese powder, and the uniaxial compressive strength of the cementitious material all significantly decreasing with the decrease of the mass ratio of activated slag, municipal sludge and waste incineration fly ash. When the mass ratio of activated slag, municipal sludge and waste incineration fly ash is between 20 and 50:30 and 60:100 (as in Table 2, the mass ratio of activated slag, municipal sludge and waste incineration fly ash = 20:30:100, 35:30:100, 50:30:100, 20:45:100, 35:45:100, 50:45:100, 20:60:100, 35:60:100, 50:60:100), the activated slag, municipal sludge and waste incineration fly ash are mixed, and during the stirring process, the organic matter and other inorganic salt substances in the municipal sludge and the inorganic chloride salts and hydroxides in the waste incineration fly ash diffuse into the activated slag, combine with the released iron and manganese substances and react with the silicon, aluminum and calcium based minerals in the activated slag. Finally, the ferric chloride content in the crude iron powder was higher than 89%, the manganese chloride content in the crude manganese powder was higher than 79%, and the uniaxial compressive strength of the cementitious material was higher than 31MPa. When the mass ratio of activated slag, municipal sludge, and waste incineration fly ash was greater than 50:60:100 (as in Table 2, the mass ratio of activated slag, municipal sludge, and waste incineration fly ash = 50:65:100, 50:70:100, 50:75:100, 55:60:100, 60:60:100, 65:60:100, and higher ratios not listed in Table 2), the activated slag and municipal sludge were excessively added, and the material matching was unbalanced, resulting in the ferric chloride content in the crude iron powder, the manganese chloride content in the crude manganese powder, and the uniaxial compressive strength of the cementitious material all significantly decreasing with the further increase of the mass ratio of activated slag, municipal sludge, and waste incineration fly ash.

[0045] Therefore, in summary, considering efficiency and cost, when the mass ratio of activated slag, municipal sludge and waste incineration fly ash is 20-50:30-60:100, it is most conducive to improving the performance of the prepared magnesium-based cementitious material and the recovery rate of iron and manganese.

[0046] Example 3 Effect of primary pyrolysis temperature on iron and manganese recovery and strength properties of prepared cementitious materials

[0047] The phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 60:100 and stirred evenly to obtain gypsum manganese slag. The gypsum manganese slag is calcined to obtain an activated slag material, wherein the calcination time is 1.5 hours and the calcination temperature is 850° C. The activated slag material, municipal sludge, and waste incineration fly ash are mixed in a mass ratio of 50:60:100 and stirred evenly to obtain an initial roasting material. The initial roasting material is subjected to continuous pyrolysis and carbonization. The pyrolysis temperature is first increased to 275°C, 300°C, 325°C, 350°C, 450°C, 550°C, 575°C, 600°C, and 625°C for a primary pyrolysis. The primary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder. The pyrolysis temperature is then increased to 1250°C for a secondary pyrolysis. The secondary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder. The solid slag obtained from the secondary pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelled material.

[0048] The strength performance test, iron content test, and manganese content test are the same as those in Example 1. The test results of this example are shown in Table 3.

[0049] Table 3 Effect of primary pyrolysis temperature on iron and manganese recovery and strength properties of prepared cementitious materials

[0050]

[0051] As shown in Table 3, when the primary pyrolysis temperature is less than 350°C (as in Table 3, the primary pyrolysis temperature = 325°C, 300°C, 275°C and lower values ​​not listed in Table 3), the primary pyrolysis temperature is low, the initial calcined material is not fully pyrolyzed, and then the secondary pyrolysis effect is affected, resulting in the ferric chloride content in the crude iron powder, the manganese chloride content in the crude manganese powder, and the uniaxial compressive strength of the cementitious material are significantly reduced as the primary pyrolysis temperature decreases. When the primary pyrolysis temperature is between 350 and 550°C (as in Table 3, the primary pyrolysis temperature = 350°C, 450°C, 550°C), the initial calcined material is continuously pyrolyzed and carbonized. During the primary pyrolysis process, the organic matter in the municipal sludge is pyrolyzed to form carbon-based materials and release active hydrocarbon gas. Active hydrocarbon gas can induce chloride salts in waste incineration fly ash to combine with iron in activated slag, resulting in carbon thermal chlorination reaction, forming ferric chloride substances that volatilize into flue gas and form crude iron powder through flue gas recovery, while phosphate and gypsum substances introduced in phosphogypsum and municipal sludge can inhibit the reaction and combination of aluminum and chlorine. During the secondary pyrolysis process, manganese in the activated slag combines with chloride salts and volatilizes on the carbon-based surface, forming crude manganese powder through flue gas recovery. In the thermal decomposition process of the slag after secondary thermal decomposition activation, the silicon-aluminum-calcium-based materials fully react with other inorganic salt minerals and complement each other to form highly active cementitious materials. Finally, the ferric chloride content in the crude iron powder is higher than 92%, the manganese chloride content in the crude manganese powder is higher than 83%, and the uniaxial compressive strength of the cementitious materials is higher than 33MPa. When the primary pyrolysis temperature is greater than 550°C (as in Table 3, the primary pyrolysis temperature = 575°C, 600°C, 625°C and higher values ​​not listed in Table 3), the primary pyrolysis temperature is too high, the material is overburned, and the impurity content in the flue gas increases, thereby affecting the secondary pyrolysis process, resulting in the ferric chloride content in the crude iron powder, the manganese chloride content in the crude manganese powder, and the uniaxial compressive strength of the cementitious material all significantly decreasing with the further increase of the primary pyrolysis temperature.

[0052] Therefore, in summary, considering efficiency and cost, when the primary pyrolysis temperature is between 350 and 550°C, it is most conducive to improving the performance of the prepared magnesium-based cementitious material and the recovery rate of iron and manganese.

[0053] The prepared crude iron powder has a maximum ferric chloride content of more than 93%, the prepared crude manganese powder has a maximum manganese chloride content of more than 85%, and the prepared high-activity gelling material has a maximum uniaxial compressive strength of up to 35Mpa.

[0054] Comparative study on the effects of different processes on the recovery of iron and manganese and the strength properties of the prepared cementitious materials

[0055] The process of the present invention is as follows: phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 60:100, stirred evenly, and gypsum manganese slag is obtained. The gypsum manganese slag is calcined to obtain an activated slag material, wherein the calcination time is 1.5 hours and the calcination temperature is 850°C. The activated slag material, municipal sludge, and waste incineration fly ash are mixed in a mass ratio of 50:60:100, stirred evenly, and an initial roasting material is obtained. The initial roasting material is continuously pyrolyzed and carbonized, the pyrolysis temperature is first increased to 550°C for a primary pyrolysis, the primary pyrolysis time is 1.25 hours, and the pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder, and then the pyrolysis temperature is increased to 1250°C for a secondary pyrolysis, the secondary pyrolysis time is 1.25 hours, and the pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder, and the solid slag obtained by the secondary pyrolysis is a gelled activated slag, and the gelled gelled activated slag is ground into powder to obtain a gelling material.

[0056] Comparative process 1: Phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 60:100, stirred evenly, and gypsum manganese slag is obtained. The gypsum manganese slag is calcined to obtain activated slag, wherein the calcination time is 1.5 hours and the calcination temperature is 850°C. The activated slag and municipal sludge are mixed in a mass ratio of 50:60 and stirred evenly to obtain the initial roasting material. The initial roasting material is continuously pyrolyzed and carbonized, and the pyrolysis temperature is first increased to 550°C for a primary pyrolysis, and the primary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder, and then the pyrolysis temperature is increased to 1250°C for a secondary pyrolysis, and the secondary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder, and the solid slag obtained by the secondary pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelling material.

[0057] Comparative process 2: Phosphogypsum and electrolytic manganese slag are mixed in a mass ratio of 60:100, stirred evenly, and gypsum manganese slag is obtained. The gypsum manganese slag is calcined to obtain activated slag, wherein the calcination time is 1.5 hours and the calcination temperature is 850°C. The activated slag and waste incineration fly ash are mixed in a mass ratio of 50:100, stirred evenly, and the initial roasted material is obtained. The initial roasted material is continuously pyrolyzed and carbonized, and the pyrolysis temperature is first increased to 550°C for a primary pyrolysis, and the primary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the primary pyrolysis process is coarse iron powder, and then the pyrolysis temperature is increased to 1250°C for a secondary pyrolysis, and the secondary pyrolysis time is 1.25 hours. The pyrolysis flue gas dust recovered in the secondary pyrolysis process is coarse manganese powder, and the solid slag obtained by the secondary pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelling material.

[0058] The strength performance test, iron content test, and manganese content test are the same as those in Example 1. The test results of this example are shown in Table 4.

[0059] Table 4 Effects of different processes on iron and manganese recovery and strength properties of prepared cementitious materials

[0060]

[0061] As shown in Table 4, the process of the present invention is significantly better than comparative process 1 and comparative process 2 in terms of iron and manganese recovery and strength performance of the prepared cementitious material.

Claims

1. A method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash, characterized in that: The following steps are involved: (1) mixing phosphogypsum and electrolytic manganese slag, and stirring evenly to obtain gypsum manganese slag; (2) calcining the gypsum manganese slag to obtain an activated slag material; (3) Mixing the activated slag, municipal sludge, and waste incineration fly ash, stirring evenly, to obtain an initial roasting material; (4) The initial roasted material is continuously pyrolyzed and carbonized. The pyrolysis flue gas dust recovered in the first pyrolysis process is coarse iron powder, and the pyrolysis flue gas dust recovered in the second pyrolysis process is coarse manganese powder. The solid slag obtained in the second pyrolysis is gelled activated slag. The gelled gelled activated slag is ground into powder to obtain a gelled material.

2. The method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash according to claim 1, characterized in that: In step (1), the mass ratio of phosphogypsum to electrolytic manganese slag is 20 to 60:

100.

3. The method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash according to claim 1, characterized in that: The calcination time in step (2) is 0.5 to 1.5 hours, and the calcination temperature is 450 to 850°C.

4. The method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash according to claim 1, characterized in that: The mass ratio of the activated slag, municipal sludge and waste incineration fly ash in step (3) is 20-50:30-60:

100.

5. The method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash according to claim 1, characterized in that: The temperature of the first pyrolysis in step (4) is 350-550° C. and the time is 0.25-1.25 hours.

6. The method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash according to claim 1, characterized in that: The temperature of the second pyrolysis in step (4) is 1150-1250° C. and the time is 0.25-1.25 hours.

7. The crude iron powder prepared by the method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash as described in any one of claims 1 to 6.

8. The crude manganese powder prepared by the method for recovering iron and manganese and preparing cementitious materials by synergistically utilizing electrolytic manganese slag and waste incineration fly ash as described in any one of claims 1 to 6.

9. The gel material prepared by the method for recovering iron and manganese and preparing gelling material by synergistically utilizing electrolytic manganese slag and waste incineration fly ash as described in any one of claims 1 to 6.

10. The gel material according to claim 9, characterized in that: The uniaxial compressive strength of the gel material is 26-35 MPa.

Citation Information

Cited By

  • Method for preparing heavy metal contaminated soil stabilizer from electrolytic manganese residues and landfill leachate and application of heavy metal contaminated soil stabilizer

    CN119799346A

  • Method for preparing heavy metal contaminated soil stabilizer by using electrolytic manganese residue and landfill leachate and application thereof

    CN119799346B

  • Method for preparing catalyst from waste incineration fly ash and electrolytic manganese residues, product prepared by method and application of catalyst

    CN120394035A

  • A method for preparing a catalyst using waste incineration fly ash and electrolytic manganese slag, and its product and application

    CN120394035B